Collaboration makes global digital libraries sustainable and ethical. Issue 1 (1st February 2019) - Chou, Charlene; Harris, Steven R.
ABSTRACT: With swiftly increasing projects of digital scholarship and digital libraries in recent years, many project leaders have shared concerns about the long‐term financial sustainability of their platforms. The lack of a long term plan of system maintenance and funding will undermine the richness and functionalities of a digital library. Project leaders express their concerns and needs about effectively allocating financial resources and subject expertise. Without strong collaborations and communications between scholars and cultural institutions, we risk duplicating efforts for similar research projects or creating gaps between the knowledge and expertise in different communities. Shareable across multilingual or multicultural communities, open access digital resources have increasing impact. However, sharing at a large scale is not without issues and challenges. This poster will present a framework to keep global digital libraries sustainable and ethical. The author proposes a workflow to create and maintain digital libraries as ecosystems, and includes a flowchart for visual presentation. Collaboration, interoperability and sustainability are key to the vision of digital libraries able to communicate with each other. When a digital library infrastructure anchors digital scholarly methods in the workflows, digital libraries will truly become a scholarly cyberspace and provide added‐value services to global users in future.